A convenient "inconvenience": The eponymous legacy of Sir William Richard Gowers (1845–1915). Issue 1 (2nd January 2017) - Toodayan, Nadeem
ABSTRACT: A century since his passing, the legacy of the great Victorian clinical neurologist, Sir William Richard Gowers (1845–1915), remains traceable to students and practitioners of medicine worldwide through eponymous medical terms named in his honor. Popular designations like "Gowers' sign" continue to lead curious minds to learn more about the pioneering neurologist's lifework and influence, and yet Gowers himself was not fond of medical eponyms. Memorably remarking that eponyms were an educational "inconvenience " in medicine, Gowers was apt to disfavor the system in the very same lecture in which he reportedly first referred to the spinal cord fasciculus that later took his name. This article will examine Gowers' own use of eponyms alongside the eponymous medical terms named for him, and, in the process, will show how Gowers' "inconvenience" may be of great service to the historically inclined modern clinician today.